The Mediating Role of Perceived Value in the Relationship Between Brand Image and Repurchase Intention: A Case Study of the Chinese Tea Market - Luo, Rui; Sriboonlue, Umawasee; Onputtha, Suraporn (Bright Publisher, 2024)
This study is dedicated to exploring how brand image influences repurchase intention through perceived value in the Chinese tea market. Five randomly selected tea brands among the top twenty tea brands in Sichuan Province were chosen as the study sample. Corporate image, product image and user image were used to measure brand image; meanwhile, functional value, emotional value, social value and price value were used to assess perceived value; and repurchase intention was directly measured through questionnaires. Six hundred valid questionnaires from consumers of these five brands were collected through the Questionnaire Star platform and analyzed by structural equation modeling using SMARTPLS 4.0 software. The results show that brand image has a significant positive effect on perceived value and repurchase intention, and perceived value plays a significant mediating role between brand image and repurchase intention. These findings not only enrich the theoretical framework, but also provide practical strategic recommendations for brand management in the Chinese tea market, emphasizing the need to pay attention to the impact of brand image on consumer repurchase intention through perceived value in the process of brand image construction and management, so as to enhance consumer loyalty and promote sustained purchase behavior.